Newsletter for Asia, the Pacific and Oceania: No. 51 September-December 2006 - International Plant Genetic Resources Institute (2006)
The APO newsletter is produced thrice a year and is mainly aimed at promoting the overall concern on genetic resources, with emphasis on their conservation and use. It provides information on genetic resources activities carried out by national programmes and other centres in the region. Information is also periodically abstracted from recent literature (books, periodicals, etc.), and brief research contributions published. With over 2500 addresses on its mailing list, the APO Newsletter is widely distributed to focus on Bioversity's mandate to advance the conservation and use of plant, animal, aquatic and microbial genetic resources for the benefit of present and future generations.